КАРНАВАЛИЗАЦИЯ И ДИАЛОГИЗМ В СОВРЕМЕННОЙ МУЗЫКЕ - Добровецкая, Эда (Acta Neophilologica, 2008)
Several ideas of M. Bakhtin’s literary theories can provide better understanding of musical works. Using Bakhtin’s concepts of carnival, dialogism and chronotope, this paper tries to analyze contemporary musical works in the genre of the concerto.